2013
DOI: 10.1093/cercor/bht060
|View full text |Cite
|
Sign up to set email alerts
|

The GABAergic Septohippocampal Pathway Is Directly Involved in Internal Processes Related to Operant Reward Learning

Abstract: We studied the role of γ-aminobutyric acid (GABA)ergic septohippocampal projections in medial septum (MS) self-stimulation of behaving mice. Self-stimulation was evoked in wild-type (WT) mice using instrumental conditioning procedures and in J20 mutant mice, a type of mouse with a significant deficit in GABAergic septohippocampal projections. J20 mice showed a significant modification in hippocampal activities, including a different response for input/output curves and the paired-pulse test, a larger long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 59 publications
5
56
0
Order By: Relevance
“…Uptake of antibodies by neurons including Purkinje cells has been recently demonstrated [11] and we confirmed antibody uptake by the AF5 rat mesencephalic cell line. Our recent in vivo studies support the cellular uptake of GAD65Ab as b78 injected in the CA3-CA1 area was detected in hippocampal interneurons [40]. Future studies are planned to investigate the cellular localization of monoclonal GAD65Ab injected in the cerebellar nuclei.…”
Section: Discussionsupporting
confidence: 61%
“…Uptake of antibodies by neurons including Purkinje cells has been recently demonstrated [11] and we confirmed antibody uptake by the AF5 rat mesencephalic cell line. Our recent in vivo studies support the cellular uptake of GAD65Ab as b78 injected in the CA3-CA1 area was detected in hippocampal interneurons [40]. Future studies are planned to investigate the cellular localization of monoclonal GAD65Ab injected in the cerebellar nuclei.…”
Section: Discussionsupporting
confidence: 61%
“…They demonstrated that context-induced reinstatement of cocaine-seeking was diminished by GABA agonists, either into the dorsal CA3 area or into the LS and VTA areas. Vega-Flores et al reported that the hippocampus has a different susceptibility to septal GABAergic inputs, depending on ongoing cognitive processes, and the GABAergic septohippocampal pathway is involved in consummatory behavior processes related to operant rewards [42]. In the present study, we demonstrated that the "nocturnal corner visit duration without drinking" was correlated with the GABA level in the hippocampus.…”
Section: Associations Between Behavioral Indices and Neurotransmittersupporting
confidence: 64%
“…Subsequently, internalization of IgGs has been confirmed in the rat cerebellum [48], in autopsied human cerebellar tissue [49], after interventricular injection of human IgGs in guinea pigs [50], and after peripheral administration of human IgGs in rats [51] (Table 2). We have confirmed the internalization of human monoclonal GAD65Ab b78 by cultured AF5 cells [35]; moreover, b78 has been detected in CA1 interneurons and PCs shortly after its injection in the medial septum/diagonal band and ipsilateral interpositus nucleus, respectively [7, 52]. Differences in neuronal cell types, antibody concentration, and detection methods may account for these contradicting results.…”
Section: Open Questionsmentioning
confidence: 67%